ChemInform Abstract: A Review on the Chemistry, Coordination, Structure and Biological Properties of 1‐(Acyl/Aroyl)‐3‐(substituted) Thioureas. Issue 21 (27th May 2014) - Saeed, Aamer; Florke, Ulrich; Erben, Mauricio F.
Abstract Review: 382 refs.